Pengaruh Guru Pendidikan Agama Kristen Sebagai Pembimbing Terhadap Pembentukan Karakter Siswa kelas IV Dan V Parlondut Tahun Pembelajaran 2023/2024 - Renta Romiama Panjaitan; Nurelni Limbong; Goklas J Manalu (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The purpose of this research is to find out how much influence Christian Religious Education Teachers as Mentors have on the Character Formation of Class IV and V Parlondut Students for the 2023/2024 academic year. The research method used is a quantitative research method. The population is all students in class IV and V of Parlondut for the 2023/2024 academic year, namely 28 people and this research is a population study. Data was collected using a positive closed questionnaire with 40 items, namely 20 items for variable 0.05,n=28) = 0.374. b) Testing a significant relationship obtained a value of tcount= 3.364 > ttable(=0.05,dk=n-2=26)= 2.056. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂="41.01"+0.38X. b) Regression coefficient of determination test (r2) = 30.3%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=16, dk denominator=n-2=28-2=26) namely 11.31 > 1.71. So it can be concluded that there is a positive and significant influence of Christian Religious Education Teachers as Guides on the Character Formation of Class IV and Parlondut Students, Samosir Regency. 2023/2024 Academic Year.